2019
DOI: 10.1111/rda.13557
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of amniotic and allantoic fluid from buffaloes during foetal development

Abstract: The objective of this study was to describe the dynamic changes in protein composition and protein abundance in amniotic and allantoic fluids from buffaloes during gestation. Amniotic and allantoic fluids were collected during the first, second and third trimesters of gestation. The foetuses were measured and weighed. Fluid samples were centrifuged at 800 g for 10 min and then at 10,000 g for 60 min at 4°C. The supernatant was collected to determine the total protein concentration. Based on total protein conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…A similar diagnosis can be observed in mares, where the up- or down-regulation of some components of fetal fluids can be indicative of a pathological condition [ 20 ]. Results from a recent study with buffalo indicated that some proteins can be in greater concentrations during the first stages of gestation, indicating that evaluations of the concentrations of these proteins can be used as a diagnostic approach for an early diagnosis of pregnancy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar diagnosis can be observed in mares, where the up- or down-regulation of some components of fetal fluids can be indicative of a pathological condition [ 20 ]. Results from a recent study with buffalo indicated that some proteins can be in greater concentrations during the first stages of gestation, indicating that evaluations of the concentrations of these proteins can be used as a diagnostic approach for an early diagnosis of pregnancy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%